White Star : a dog on the Titanic - Crisp, Marty (New York : Scholastic, 2006)
Twelve-year-old Sam, a passenger on the Titanic's maiden sea voyage, volunteers to help care for the dogs in the ocean liner's kennel and becomes fast friends with the Irish setter of J. Bruce Ismay, the ship's owner.
"Apple paperbacks."
Includes bibliographical references (p. 145-146).
6.3
3-6
Keywords: Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction; Shipwrecks -- Fiction; Irish setters -- Fiction; Dogs -- Fiction; Survival -- Fiction; Titanic (Steamship) -- Fiction; Shipwrecks -- Fiction; Irish setters -- Fiction; Dogs -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction